FORMATION OF CREATIVE SKILLS IN JUNIOR SCHOOL CHILDREN IN FINE ARTS LESSONS - Gulmira Jumaniyazovna Arslanova; Ksenia Vitalievna Azarova (European Science Publishing, 2024)
This article reflects research on the use of interactive pedagogical technologies to develop creativity among elementary school students in fine arts lessons. The positive impact of various innovative techniques on improving children's creative abilities is analyzed. Attention is focused on the practical application of these techniques in the educational process.
Keywords: fine arts, students, non-traditional lesson, development, education, creativity, method, creative abilities.